Determinants of Revenue Growth among Marketplace SMEs: Evidence from Production Factors in Indonesia - Keyla Ceceliananda Putri; Ali Zainal Abidin (STIE Amkop Makassar, 2026)
This research endeavor seeks to examine the influence of production determinants and technological openness on the income progression of micro, small, and medium enterprises (MSMEs) engaged in marketplace activities within Indonesia. The investigation utilizes a quantitative methodology, drawing upon microdata derived from the 2023 E-Commerce Survey executed by Statistics Indonesia (BPS) via the VECOM24 S dataset. The analytical framework employed is binary logistic regression, with marketplace income growth designated as the dependent variable. The independent variables under consideration encompass capital, labor, the duration of online business operation, and technology training. The outcomes reveal that labor exerts a positive and statistically significant impact on marketplace income growth, whereas the duration of online business operation and technology training yield negative and statistically significant effects. In contrast, capital does not demonstrate a significant influence on the income growth of MSMEs. These results suggest that digital adaptability and business management proficiency hold greater importance than extensive digital experience or general technology training in enhancing the performance of marketplace-oriented MSMEs in Indonesia.